Knowledge and awareness of basic life support among MBBS students in tertiary care hospital in Uttar Pradesh - Gupta, Bikram K.; Tomar, Shubham; Karn, Anukul; Singh, Jassimran; Agrawal, Aditi; Mhaske, Vanita R. (International Journal of Research in Medical Sciences, 2020)
Background: Every medical student in India have to undergo a compulsory rotatory internship for completion of their course where they encounter various medical emergencies and apply their medical knowledge. An early encounter to a basic life support course and training will increase the efficacy of cardiopulmonary resuscitation and thus the outcome of the patient. This study was designed to test knowledge of MBBS students in a tertiary care hospital. Methods: This observational study was conducted in a tertiary care hospital in Uttar Pradesh and used a preformed validated questionnaire to test awareness and knowledge of basic life support and cardiopulmonary resuscitation in a sample of 500 MBBS students. Descriptive analysis was performed on the questionnaire responses. All data obtained from the questionnaire was evaluated and statistically analysed using software IBM SPSS Statistics software version 24 (IBM Corp., Armonk, NY, USA) for MS windows. Results: With a response rate of 47% among 500 MBBS students, the mean score obtained was 2.34±1.066 out of a maximum score of five. A maximum score of 2.804±1.055 obtained by 5th-year students. Surprisingly, first-year students achieved an average score of 2.66±0.97, which was higher than that of 2nd, 3rd, and 4th year students. 87% of students were like-minded to participate in the cardiopulmonary resuscitation (CPR) awareness program. Only 45% of students correctly answered the order of CPR as C-A-B (chest compression-airway-breathing). Conclusions: The study showed that though the awareness and importance of basic life support (BLS) are high among the medical students, the accurate knowledge required in performing BLS is inadequate. This study also showed that the National medical commission has taken a positive step in the incorporation of BLS in the curriculum.